A training tool for system dynamics and continuous simulation - Ng, Patsy. (2008)
In this project, system dynamic modelling tool, Ithink, was used to model dynamic systems and their behaviours. Their basic structure building blocks were illustrated and the "Bath Tub" model was used as an example to introduce the fundamental basic concept of model building. Systems with different input and output functions were modelled and analysed. In addition, the unique characteristic behaviours of positive feedback and negative feedback were studied.